Thyroid Hormones and Reproductive System Characteristics in Humans and Laboratory Animals - Taresh, Ammar Issa (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Thyroid hormones (THs) are vital for the development and function of various physiological systems, including the reproductive system, in both humans and animals. Specific Background: Disruptions in TH levels, due to disease or environmental toxicants, have been implicated in fertility issues, pregnancy outcomes, and postnatal development. Knowledge Gap: However, comparative data on how thyroid dysfunction affects human versus rodent reproduction remain limited, particularly concerning mechanistic pathways and developmental endpoints. Aim: This study aimed to evaluate and compare the effects of thyroid hormone imbalances on the reproductive systems of humans and laboratory animals, focusing on both genomic and nongenomic mechanisms. Results: Findings show that both hypothyroidism and hyperthyroidism disrupt reproductive hormone balance, gametogenesis, and sexual development, though the severity and pathways differ between species. Animal testing protocols revealed species-specific responses in thyroid hormone metabolism, signaling, and reproductive outcomes. Novelty: The research integrates genomic-nongenomic TH pathways, evaluates reproductive endpoints in endocrine-disruptor assays, and compares species-specific thyroid function. Implications: These findings underscore the importance of refining animal models and screening protocols for better prediction of human reproductive risks, advocating for inclusion of thyroid-sensitive parameters in regulatory toxicity assessments.Highlight : Thyroid hormones play critical roles in reproductive system development in both humans and lab animals. Hypo- and hyperthyroidism significantly affect fertility, menstrual cycles, and hormonal balance. Rodent models offer insights but may not fully replicate human thyroid physiology. Keywords : Thyroid Hormones, Reproduction, Hormone Receptors, Thyroid Dysfunction, Rodent Models